Crack damage detection of reinforced concrete beams using local stiffness indicator - Ismail, Z.; A. Z. C., Ong; Abdul Ghaffar, Abdul Rahman (Academic Journals, 2011)
This paper described the application of the generalized solution for transverse vibration to detect crack damages in reinforced concrete beams. A single crack was induced in a full-scale reinforced concrete beam by application of a point load. The load was increased in stages to obtain different crack heights to represent the extent and severity of the defect. Experimental modal analysis was performed on the beam prior to application of the load and after each load stage. The mode shape equation for the beams was obtained by using nonlinear regression. Global flexural stiffness was derived by utilizing the regressed variable  into the equation for transverse vibration of a Bernoulli-Euler prismatic beam. Local flexural stiffness at each coordinate point was derived by substituting the regressed data at that point and by using the centered-finite-divided-difference formula. The global stiffness decreased with increased severity of the crack in the beam. The results were compared with values computed using the secant modulus from the load-deflection plot obtained upon loading at each load stage and the trend was similar. The proposed algorithm could form the basis of a technique for structural health monitoring of load induced damaged reinforced concrete structures.